Biosurfactants production by yeasts using soybean oil and glycerol as low cost substrate - Accorsini, Fábio Raphael [UNESP]; Mutton, Márcia Justino Rossini [UNESP]; Lemos, Eliana G. Macedo [UNESP]; Benincasa, Maria [UNESP] (FapUNIFESP (SciELO), 2012)
Biosurfactants are bioactive agents that can be produced by many different microorganisms. Among those, special attention is given to yeasts, since they can produce many types of biosurfactants in large scale, using several kinds of substrates, justifying its use for industrial production of those products. For this production to be economically viable, the use of residual carbon sources is recommended. The present study isolated yeasts from soil contaminated with petroleum oil hydrocarbons and assessed their capacity for producing biosurfactants in low cost substrates. From a microbial consortium enriched, seven yeasts were isolated, all showing potential for producing biosurfactants in soybean oil. The isolate LBPF 3, characterized as Candida antarctica, obtained the highest levels of production - with a final production of 13.86 g/L. The isolate LBPF 9, using glycerol carbon source, obtained the highest reduction in surface tension in the growth medium: approximately 43% of reduction after 24 hours of incubation. The products obtained by the isolates presented surfactant activity, which reduced water surface tension to values that varied from 34 mN/m, obtained from the product of isolates LBPF 3 and 16 LBPF 7 (respectively characterized as Candida antarctica and Candida albicans) to 43 mN/m from the isolate LPPF 9, using glycerol as substrate. The assessed isolates all showed potential for the production of biosurfactants in conventional sources of carbon as well as in agroindustrial residue, especially in glycerol.
Keywords: Yeast; Biosurfactants; Glycerol; Soybean oil